Prevalence Of Diabetes And Association Of Fasting And Postprandial Glucose With Hba1c, 6-Year Study In Reference Laboratory - Gohil, Sanjay; Singh, Preeti; Kambli, Megha; Haryan, Reshma; Jatale, Raj; Dixit, Rakhi Bajpai; Chadha, Kirti (Annals of Pathology and Laboratory Medicine, 2023)
Background Prevalence of diabetes is estimated in the Indian population using hemoglobin A1c (HbA1c) data collected over the period of 6 years, in the Metropolis Reference Laboratory Mumbai. HbA1c values with gender and age structure was correlated during fasting and postprandial glucose for the non-diabetic, pre-diabetic, and diabetic populations in terms of frequency and percentile. Method Retrospective analysis of HbA1c data obtained in a referral laboratory based in Mumbai over a span of 6 years from 2015 to 2020. A total of 2,94,264 cases were divided in six age groups i.e. 15-20Y, 21-30Y, 31-40, 41-50, 51-60, and >60Y. High-performance liquid chromatographic separation and quantification of HbA1c in blood with gender and age were done. HbA1c values were also correlated with glucose fasting and postprandial in the studied population. Results Prevalence of diabetes (HbA1C >6.5) was 57.60% in the studied population. The incidence and prevalence of HbA1c in the diabetic range were highest in the age group of >60 years. Males showed a higher prevalence of diabetes than females, while females are found to be more pre-diabetic. A significant (p>0.001) positive linear correlation was found between HbA1c with fasting and postprandial glucose, respectively. Conclusion The age group of >60Y showed a maximum diabetic prevalence. Gender disparity was recorded more in males than females having higher HbA1c. The sensitivity of HbA1c is comparable with fasting and postprandial glucose. However, HbA1c cannot replace plasma glucose estimation and could be used in conjunction with fasting and postprandial glucose for proper diagnosis and disease management.